THERMOELECTRIC DEVICE FOR TREATMENT PANARIATION - V. I. Dvorjanchikov; D. A. Magomedov; K. A. Magomedova; I. Sh. Mispahov (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives The aim of the study is to develop a thermoelectric device for the treatment of felon, its mathematical modeling, experimental tests of the laboratory model of the device, the study of thermal processes occurring in it. Method. A design of a thermoelectric device for the treatment of felon, providing the possibility of both uniform and contrasting therapeutic heat effects on the fingers is proposed. Result. A mathematical model of the device has been developed, implemented on the basis of solving a non-stationary two-dimensional heat conduction problem for a system of complex configuration with boundary conditions of the second and third kind. Experimental studies of the device were carried out on a specially designed test bench for checking the adequacy of the mathematical model. A two-dimensional non-stationary heat conduction problem was solved for a complex system with a rectangular geometry of fragments and heat sources. The temperature change of various points of the “device-object” system of exposure in space and in time at various values of the cooling and heating capacity of a thermoelectric battery (TEB) was studied. Comparison of calculated and experimental data. Conclusion. The results of research have shown the effectiveness of the use of the developed device for the implementation of thermal procedures in the treatment of felon in terms of efficiency, versatility, impact reliability, comfort and accuracy of maintaining temperature conditions. It is shown that it is possible to increase the efficiency of the device using a combination of thermopile operation modes (maximum cooling capacity and maximum coefficient of  performance), as well as improving the intensity of heat removal from its reference junctions.